Agro-Economics of Sub-Saharan Africa : the Nigerian Case - Singh, I J (Annals of Arid Zone, 2016)
Assuming a modest growth rate of 3% per annum, the estimated population of Nigeria (about 104 million in 1984) is expected to be 166 million by 2000 AD. The profitability of agriculture is highly vulnerable due to low level of fertilizer use, low crop yields and low product prices. Sorghum, millet and cowpea form the common crop mixture in the rainfed areas of Nigeria. The per hectare net incomes from the three crops wee US $ 25, 50, 283. 91 and 48. 28, respectively making a total net income of 357. 69 dollars per hectare from the crop mixture. The estimated annual family living expenses for a family of 5 adults were 2, 647 dollars at the 1983 price level. The estimated annual family living expenses for a family of 5 adults were 2, 647 dollars at the 1983 price level. Thus, a total net income of US $ 357. 69 per hectare from a crop mixture makes a farm size of 7.4 ha a minimum necessity to just meet the annual family living expenses. Very poor agricultural growth against the population increase made Nigeria's food imports to be over 2 billion dollars a year since 1985. The food imports, and particularly the imports of rice have discouraged production of cheaper home-grown crops such as yam, gari and maize. The estimated per capita availability of cultivable land in 1984 was 0. 78 ha which is likely to be reduced to 0. 54 ha by 2000 AD. The availability of cultivable land is sufficient to produce balanced food and attain self-sufficiency in food production. Nigeria's soaring food imports could be minimized by exploiting fresh and inland water resources for fish farming, increasing domestic milk and meat production with the help of the age-old expertise of the "Fulanis", and by producing cheaper substitutes for meat from soybeans.